The Bible, Disability, and The Chosen - Burnette-Bletsch, Rhonda (Interpretation, 2024)
Biblical healing stories, especially when subjected to ableist interpretations, can fuel discriminatory attitudes toward people with disabilities. The Chosen series has opted to address issues of disability directly, not only by adapting healing stories from the Gospels, but also by creating storylines to depict other people with disabilities, including two of the twelve disciples. This article uses film criticism and disability studies to examine depictions of disability in The Chosen over the course of its first three seasons.